SYNTHESIS, CHARACTERIZATION AND APPLICATION OF MEETHAMPHETAMINE – IMPRINTED POLYMERIC SOLID-PHASE - Y. K. Al-Bayati (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was determine methamphetamine by the addition to the glycidyl methacrylate (GMA) monomer resulting from bulk polymerization formation. To acquire the highest adsorption capacity, molar ratios of the template, monomer, and cross-linking agent, as well as solvents and multiple monomers were investigated. Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were used to analyze the Methamphetamine polymer. The elution of Methamphetamine had a small effect on the surfaces of the three-dimensional network structure. Methamphetamine was successfully eluted using a mixture of methanol and acetic acid. The Methamphetamine adsorption capacities were 3.8145 and 9.01773 mol/g (Qmax), respectively. A Langmuir isotherm model follows Methamphetamine adsorption. Solid-phase extraction (SPE) syringes packed with molecular imprinted polymers (MIPs) were used to selectively separate and preconcentration the Methamphetamine from different patients.